The IHSAN Model: Integrating the DIKW Framework into Higher Education Curricula for Tawhidic Resilience (An Integrative Review) - Ashary Ramdhani; Siti Maryam Munjiat; Pandu Pribadi (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: The pervasive secular-modern paradigm in higher education has created a severe epistemological dichotomy between empirical science and religious doctrine, contributing to a crisis of meaning and future anxiety among university students. Objective: This study aims to conceptually develop a novel curriculum architecture that synthesizes modern data hierarchies with Islamic epistemology to cultivate existential resilience. Methods: Employing an integrative literature review approach, this research systematically evaluated multidisciplinary texts across theology, psychology, and educational management utilizing an iterative thematic synthesis to construct a cohesive pedagogical framework. Results: The findings reveal that integrating the data, information, knowledge, and wisdom hierarchy with classical Islamic intellects transforms mechanical learning into profound spiritual wisdom. This integration serves as a robust meaning-making system, generating Tawhidic Resilience, which acts as a divinity-based psychological fortitude. By reframing scientific inquiry as a transcendental spiritual instrument, students develop positive religious coping mechanisms that suggest potential to support the mitigation of psychological distress and moral neuroticism. The discussion highlights the necessity of shifting educators' roles toward spiritual mentorship and emphasizes the implementation of interdisciplinary project-based learning. Conclusion: The study concludes that addressing the psychological vulnerabilities of modern learners requires a holistic curriculum paradigm shift centered on the IHSAN Model and Tawhidic Resilience framework. The proposed model provides a critical theoretical foundation for institutionalizing integrated curricula, enabling Islamic higher education to produce graduates who are both intellectually competent and spiritually resilient.